Bereavement Photography for Children: Program Development and Healthcare Professionals’ Response - Michelson, Kelly Nicole (2013)
Reports of in-hospital bereavement photography focus largely on stillborns and neonates. Empiric data regarding the implementation of bereavement photography in pediatrics beyond the neonatal period and the impact of such programs on healthcare professionals (HCPs) is lacking. We describe the implementation of a pediatric intensive care unit (PICU) bereavement photography program and use questionnaire data from HCPs to describe HCPs’ reflections on the program and to identify program barriers. From July, 2007 through April, 2010 families of 59 (36%) of the 164 patients who died in the PICU participated in our bereavement photography program. Forty questionnaires from 29 HCPs caring for 39 participating patients/families indicated that families seemed grateful for the service (n=34, 85%) and that the program helped HCPs feel better about their role (n=30, 70%). Many HCPs disagreed that the program consumed too much of his/her time (n=34, 85%) and that the photographer made his/her job difficult (n=37, 92.5%). Qualitative analysis of responses to open ended questions revealed four categories: the program’s general value; positive aspects of the program; negative aspects of the program; and suggestions for improvements. Implementing bereavement photography in the PICU is feasible though some barriers exist. HCPs may benefit from such programs.